TINJAUAN YURIDIS TERHADAP PERJANJIAN KREDIT USAHA PEDESAAN ANTARA BANKALTIM DENGAN MASYARAKAT PEDESAAN DI KECAMATAN SANGA SANGA KABUPATEN KUTAI KARTANEGARA - Eko Prasetyo Kurniawan (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTCredit is a product and services that provide substantial profits for the bank, especially credit interest,  it has greater profits than anothers service products of Bankaltim.The research of this study was purposed to determine the development of the credit amount, the amount of revenue and provision of credit in terms of increased Bankaltim in Sanga-Sanga.The object of research that is used in the preparation of this thesis is about the provision of credit in increasing revenue at Bankaltim in Sanga-Sanga, The method used is descriptive analysis. Descriptive analysis is research that describes the object of research based on facts  that are ongoing, by collecting, composing and explain the data obtained by the research techniques include the form of observations.The results showed that the provision of credit could increase Bankaltim Sanga-sanga revenue.